A Study on Non-Fungible Tokens Marketplace for Secure Management - Rishabh, Singh; Chitra, K.; Yap, Choi Sen (INTI International University, 2024)
The secure management and sale of digital assets has become a critical problem in an increasingly digitized environment. This project intends to address this issue by creating decentralized applications (dApps) that use blockchain technology to provide secure and efficient digital asset management, with a focus on NFTs. The NFT marketplace includes secure wallet connections, NFT image creation, minting, the marketplace, and profile management. Solidity-based smart contracts are utilized to create the NFT Marketplace back end, and IPFS is used for storage. The NFT Marketplace's front-end development uses React JSX and the web3js framework, allowing developers to connect to the Ethereum network. NFT Marketplace may assist creators in selling their art through a smart contract system, in which the artwork's ownership transfers to the new owner upon submission of a digital certificate.